Zastosowanie kompostowania do przetwarzania frakcji organicznej odpadów komunalnych = Application of composting to processing of organic fraction separated from municipal waste - Sidełko, Robert; Szymański, Kazimierz; Walendzik, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article a results of investigation tracked to qualify possibitity of processing of organic fraction separated from municipal waste has been presented. The research of waste structural was carry in Koszalin. A factor witch has been taken into consideration to have representive samples was differences between infrastructure of commune.
Keywords: odpady komunalne; frakcja organiczna; stabilizacja; kompostowanie; municipal waste; organic fraction; stabilization; composting